Bringing planning back into the picture – How can supply chain planning aid in dealing with supply chain-related problems in construction?. Issue 8 (3rd August 2018) - Thunberg, Micael; Fredriksson, Anna
Abstract: There are several supply chain-related problems facing the construction industry, such as poor construction site logistics, lack of communication and trust. These problems can jeopardize construction projects through delays and cost overruns. Supply chain planning, a part of supply chain management (SCM), can be used as a tool to deal with these problems. The purpose of this paper is to study how linkages between common supply chain-related problems in construction can be illustrated and to demonstrate how they could be resolved through supply chain planning. Firstly, we identify how the linkages between common problems can be illustrated, and secondly the role of supply chain planning in resolving these problems. A conceptual model is developed that was verified using three cases with Swedish gypsum and kitchen supply chains. The model is shown to be useful in illustrating how supply chain problems occurring at executional level on-site are related to problems originating in lack of planning at company/pre-construction level. The study thus demonstrates how supply chain planning can aid in resolving supply chain problems. The paper contributes by bringing planning back into the picture and by showing how supply chain planning can help to adopt SCM in construction.